Cassino '44 the brutal battle for Rome - Holland, James 1970- (Atlantic Monthly Press, 2024)
"Acclaimed World War II historian James Holland vividly relates the dramatic last months of the Italian Campaign in a masterful volume that brings new awareness to this vital hinge point of the war. As the new year of 1944 began in Italy, the Allied army's momentum had ground to a halt just south of the vaunted German Gustav Line of defense, far short of their initial objective of liberating Rome by Christmas. The fighting up the Italian peninsula had been brutal-rugged terrain, fierce resistance, terrible weather. While Allied leaders in London prepared for the cross-Channel invasion of France later that spring, the war in the West hinged in Italy.
Keywords: Schlacht um Montecassino; Cassino, Battle of, Cassino, Italy, 1944; World War, 1939-1945 / Campaigns / Italy; Rome / Strategic aspects; Italy / History / Allied occupation, 1943-1947; Bataille de Cassino, Cassino, Italie, 1944; Guerre mondiale, 1939-1945 / Campagnes et batailles / Italie; Italie / Histoire / 1943-1947 (Occupation alliée)